Efektivitas Undang-Undang Pengelolaan Zakat Pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Tanjung Jabung Timur - Prasetio Febrianto; Evalina Alissa (Zaaken: Journal of Civil and Business Law, 2020)
The purpose of this research is 1). To know and analyze the effectiveness of the Law on the management of Zakat on the national Amil Zakat Agency (BAZNAS) east Tanjung Jabung Regency; 2). To know and analyze the obstacles in the management of Zakat on the national Amil Zakat Agency (BAZNAS) east Tanjung Jabung Regency based on the law on the managing of Zakat. The problem formulation of the research is 1). Is the management of zakat on the body of Amil Zakat Nasional (BAZNAZ) Kab. East Tanjung Jabung is effective under the Zakat Management Act; 2). What is the constraint in the management of Zakat on the national Amil Zakat Agency (BAZNAS) Kab. Tanjung Jabung East based on the law on Zakat management. Empirical research type. Research result 1). The management of Zakat funds is not carried out effectively, because of the small amount of zakat that can be collected by the National agency of Amil Zakat (BAZNAS) east Tanjab Regency; 2). There are 4 Zakat fund management constraints namely: 1). There is a crisis of public confidence in the government of; 2). There is a pattern of view on the implementation of zakat which is generally more enthusiastic about zakat Fitrah; 3). The small amount of zakat fund that can be collected BAZNAZ 4). The number of zakat organizations are formed not under the Law on Zakat management. Keywords: Zakat Management in Amil Zakat Agency; Tanjung Jabung Timur Regency. Abstrak Tujuan penelitian ini adalah 1).Untuk mengetahui dan menganalisis Efektivitas Undang- Undang tentang Pengelolaan Zakat padaBadanAmilZakatNasional (BAZNAS) Kabupaten Tanjung Jabung Timur; 2). Untuk mengetahui dan menganalisis kendala dalam pengelolaan zakat pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Tanjung Jabung Timur berdasarkan Undang-Undang tentang pengolaan zakat. Rumusan masalah dari penelitian adalah 1).Apakah pengelolaan zakat pada badan amil zakat nasional (BAZNAZ) Kab.Tanjung Jabung Timur telah Efektif berdasarkan Undang-Undang Pengelolaan Zakat; 2). Apa yang menjadi kendala dalam pengelolan zakat pada Badan Amil Zakat Nasional (BAZNAS) Kab. Tanjung Jabung Timur berdasarkanUndang-UndangtentangPengelolaanZakat. TipePenelitian YuridisEmpiris. HasilPenelitian: 1).Pengelolaan dana zakat tidak terlaksana dengan efektif, karena kecilnya jumlah zakat yang mampu dihimpun oleh Badan Amil Zakat Nasional (BAZNAS) Kabupaten Tanjab Timur; 2). Terdapat 4 Kendala Pengelolaan dana zakat yaitu: 1).Adanya krisis kepercayaan masyarakat terhadap pemerintah ; 2). Adanya pola pandangan terhadap pelaksanaan zakat yang umumnya lebih antusias pada zakat fitrah; 3). Kecilnya jumlah dana zakat yang mampu dikumpulkan BAZNAZ; 4).Banyaknyaorganisasizakatyangdibentuk tidak berdasarkan Undang-Undang tentang Pengelolaan Zakat. Kata Kunci: Pengelolaan Zakat Badan Amil Zakat Nasional; Kabupaten Tanjung Jabung Timur.